2022
DOI: 10.3390/ijerph19105915
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Joint Biomechanics of Different Skill Level Practitioners in Chen-Style Tai Chi Punching

Abstract: Purpose: “Yan Shou Hong Cui” is a representative punch in Chen-style Tai Chi. The training is an important factor in affecting the effect of Tai Chi practice. Joint angles are the most intuitive way to evaluate motion. The purpose of this study is to compare the movements of Tai Chi masters and beginners’ movements through the analysis of joint angle and punching effect, and explore the influence of training years on the power generation of Tai Chi punches. Methods: There were 14 Chinese Chen-style Tai Chi sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Bobath exercise improves walking ability and reduces spasticity ( 41 ). In Tai Ji, all body movements are directed by the waist, which serves as an axis for limb movements ( 25 , 42 ). Since trunk control is commonly reduced post-stroke, electro-myography (EMG) study reported that the paretic side demonstrated slower, lower EMG recruitment timing and magnitude ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bobath exercise improves walking ability and reduces spasticity ( 41 ). In Tai Ji, all body movements are directed by the waist, which serves as an axis for limb movements ( 25 , 42 ). Since trunk control is commonly reduced post-stroke, electro-myography (EMG) study reported that the paretic side demonstrated slower, lower EMG recruitment timing and magnitude ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, a single set in a typical ACSM-style resistance training routine requires an average of 4.52 Kcal/min ( 43 ). Research by Hua and colleagues mapped the striking force of Chen-style Taijiquan ( 44 ), illustrating its impact on upper-body strength development. The philosophy of Taijiquan revolves around motion within stillness and overcoming hardness with softness.…”
Section: Discussionmentioning
confidence: 99%
“…Taijiquan was created as a form of combat skill, and it was never intended to be a gentle form of exercise, even though its modern motion appears slow and graceful during practice. As a result, its practitioners are expected to develop whole-body strength even for recreational purposes [ 33 ], and its combat power is augmented by a type of penetrating hand strike [ 34 ]. Neither is the present finding isolated.…”
Section: Discussionmentioning
confidence: 99%